Analisis Pendekatan Struktural Puisi “Waktu” Karya Heri Isnaini - Dyvia Saumi Putri; Shintia Ananda (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Poetry is a type of literature whose language is bound by rhythm, spell, rhyme, and arrangement of lines and stanzas. Usually poetry contains the author's expressions about emotions, experiences and impressions which are then written in good language so that they are acceptable and pleasant to read. In the structural approach there is a physical structure and an inner structure. The physical structure of poetry is a method of conveying the essence of poetry which consists of facial expressions, diction, images, concrete words, figures of speech, and rhymes or rhythms. Meanwhile, the inner structure consists of; theme, tone, feeling or feeling, and mandate. This analysis aims to analyze the physical structure and inner structure contained in the poem